1998
DOI: 10.1097/00004694-199805000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: It is well known that significant differences exist in the anthropometric data of different races and ethnic groups. This is a cross-sectional study on segmental bone length based on 3,647 Chinese children of equal sex distribution aged 3-18 years. The measurements included standing height, weight, arm span, foot length, and segmental bone length of the humerus, radius, ulna, and tibia. A normality growth chart of all the measured parameters was constructed. Statistical analysis of the results showed a very hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Tanner et al [5] described the distal-to-proximal growth gradient in adolescents: distal body parts have their pubertal growth spurt earlier in adolescence in comparison to more proximal body parts. This theory from the 1960s was investigated by other researchers and indeed different ages were found for the PGV of the different body length dimensions [68]. The peak growth of, for example, foot length or subischial leg length preceded the peak growth of sitting height and this might be useful in determining the age of the PGV of sitting height in advance.…”
Section: Introductionmentioning
confidence: 90%
“…Tanner et al [5] described the distal-to-proximal growth gradient in adolescents: distal body parts have their pubertal growth spurt earlier in adolescence in comparison to more proximal body parts. This theory from the 1960s was investigated by other researchers and indeed different ages were found for the PGV of the different body length dimensions [68]. The peak growth of, for example, foot length or subischial leg length preceded the peak growth of sitting height and this might be useful in determining the age of the PGV of sitting height in advance.…”
Section: Introductionmentioning
confidence: 90%
“…Arm span measurements are particularly important to record in addition to height gains in patients with scoliosis because curve deterioration may cause a reduction in overall height, and thus, mask the actual spine growth achieved [ 22 ]. Regardless, the correlation between arm span and standing height is nearly identical, so any change in arm span is quite representative of the height gains [ 51 ]. One study suggested that standing height is ~97% of arm span, with boys having a slightly greater proportion than girls [ 52 ].…”
Section: Growth Measurementsmentioning
confidence: 99%
“…Additionally, Stevenson ( 5 ) used TL measurement to estimate the height of children with moderate CP aged up to 12 years old. In another study, TL measurement was used to estimate the height of children aged 3–18 years in China but only among healthy children ( 8 ) . In addition, these equations have not been validated as suitable for Malaysian CP children, and thus, the malnutrition may be over or underestimated.…”
Section: Introductionmentioning
confidence: 99%